Biological thermophilic post hydrolysis of digestate enhances the biogas production in the anaerobic digestion of agro-waste. (December 2020) - Bolzonella, D.; Battista, F.; Mattioli, A.; Nicolato, C.; Frison, N.; Lampis, S.
Abstract: A thermophilic post-hydrolysis process was applied to the effluent digestate of an anaerobic digester treating agro-waste to further solubilize biorecalcitrant organic polymers and, by recirculating back hydrolysate to the anaerobic reactor, increase the biogas production. The thermophilic reactor operated at 3 days hydraulic retention time determined a clear increase in the concentrations of both soluble organic matter (as COD) and volatile fatty acids: concentrations increased by 25% and 65%, respectively. As a consequence, the recirculation of this post-treated stream to the digester determined an increase in biogas production of 30% on average with respect to the case without thermal post treatment. Graphical abstract: Image 1 Highlights: Biomass rich in lignocellulose is only partially biodegradable in anaerobic conditions. Biological post-hydrolysis enhances degradation of residual lignocellulosic material in digestate. Increased biogas recovery is possible when thermally treated digestate is sent back to the anaerobic digester. Surplus biogas production after thermal post-hydrolysis can reach 30%. The studied process allows for the generation of 2584 PJ via anaerobic digestion of lignocellulosic biomasses.